SUPPLY RESPONSE OF FRESH MILK IN SRI LANKA - Sarujan, S.; Sooriyakumar, K.; Sivashankar, S. (My University, 2018)
Cows by providing better veterinary services and better cattle management at farm level will significantly increase the milk production. And also this study would be useful to the policy makers to examine the changes in producer surplus for a shift in supply or demand of fresh Domestic milk production in Sri Lanka is sufficient only to meet around 40 percent of the local requirement at current consumption rate. The balance is supplied by imports. The annual per capita consumption of milk in Sri Lanka is about 46 kg. Sri Lankan fresh milk consumption is very low compared to India and Pakistan in the South East Asia region. However, consumption of fresh milk in Sri Lanka appears to increase with income. This could shift demand for dairy products towards liquid milk. This presents good opportunities for smallholders who are involved in domestic dairy production. The need to develop the industry is further stressed due to its ability to contribute considerably to Sri Lanka’s economic development and uplifting the livelihood of an estimated 3.5 million smallholders in the sector. Sri Lanka mainly imports milk products in the form of milk powder. It indicates that domestic producers have a comparative advantage in the liquid milk market. Considering all, it is obvious that there is a need to increase the domestic supply of milk and hence, this study develops a fixed effect panel regression model for the supply response of fresh milk in Sri Lanka using district level panel data. For this study, district–wise annual data of daily average milk production, average producer price of fresh milk, number of milking cows and number of milk collection center was collected for the time period 2010 to 2015 from the Department of Census and Statistics. The result of this study indicates that a 10% increase in producer price of milk, number of milking cows and number of milk collection center will increase daily average milk production in the each district by around 8%, 7% and 2.5% respectively while other things being equal. This study suggests that increasing the milk collecting center in each district will encourage farmers to produce more milk and increasing number of milking milk.
Keywords: Supply Response; Fresh Milk; Panel Regression Model